All-sky census of galactic open cluster stars - Kharchenko, N.V.; Piskunov, A.E.; Roser, S.; Schilbach, E.; Scholz, R.-D. (Кинематика и физика небесных тел, 2005)
We present the results of a systematic study of the wider neighbourhoods of 520 Galactic open clusters from data of the all-sky high-precision homogeneous catalogue ASCC-2.5. About 30 000 members have been selected on the basis of proper motion, photometric and spatial criteria. Angular and linear sizes of cluster cores and coronas, mean cluster proper motions in the Hipparcos system, distances and ages are derived for all clusters, including some 200 clusters, for which distances and ages have been obtained for the first time. Mean radial velocities are computed for about 300 clusters (for about 100 clusters for the first time). The typical cluster radii are found to be more than two times larger than previously published values. The catalogue of cluster parameters is supplemented by a catalogue of 171 000 stars located in 520 cluster areas and by an atlas of diagrams for each individual cluster.